Menimbang Kewenangan DPR dalam Penggunaan Hak Angket Pada Kasus Korupsi KTP Elektornik - Firdaus, Fahmi Ramadhan; Anggono, Bayu Dwi (University of Jember, 2019)
In Indonesia, the control function of the House of Representatives (DPR) includes interpellation rights, inquiry rights and the right to express opinions. In 2017, the DPR's inquiry rights to the Corruption Eradication Commission (KPK) were considered unconstitutional because the law did not include the KPK as the object of the inquiry mechanism. However, the Constitutional Court (MK) in Decision Number 36 / PUU-XV / 2017 defined KPK as an executive so that this institution can be monitored through the inquiry mechanism. This court's decision, however, contradicts to the four previous decisions which classified KPK as an independent institution. This article examines the validity of the DPR's inquiry rights to the KPK by considering the DPR's inquiry rights as a form of a mechanism for mutual checks and balances to the other state institutions. In practice, there are both formal and material rules that must be fulfilled so that their implementation is legally valid and the DPR's inquiry rights to the KPK in cases of the electronic KTP corruption ignore these conditions. This article recommends that the DPR be careful when using inquiry rights as a monitoring mechanism. Keywords: Inquiry rights, House of Representatives, Corruption Eradication Commission